PSXVI-33 Evaluation of the microbiome of mares' milk through lactation. (7th December 2018) - Gordon, M; Jacobs, R
Abstract: Classically, the nutrients in milk have been studied as critical components to support growth. Recently, other factors have been identified for their role in supporting neonatal nutrition. Once thought to be sterile, milk is known to be populated by numerous microbes, an important factor related to the development of the foals' gastrointestinal microbiome. It is believed that the initial inoculum comes as the foal passes through the vaginal canal and continues as the foal interacts with its environment, and consumes milk. The objective of this study was to evaluate the bacterial population of mares' milk. Samples were evaluated and bacterial population data was correlated to the age, BW, and BCS of the mare, days of lactation, offspring gender, and physiological growth measurements of the foal. Eight multiparous Quarter Horse mares foaled naturally and milk samples were obtained aseptically at 36 hr, 70 d, and 136 d post foaling. Mares were offered 8 lb of concentrate (Purina® Ultium Growth®) 2x/d and 18 lb of hay with free choice access to water and salt. Microbial DNA was extracted and PCR amplified prior to sequencing utilizing an Illumina® MiSeq® platform. Bacterial diversities were determined based on OTU assignment between and within samples. Data were analyzed via ANOVA using the MIXED procedure of SAS. 94.57% of reads were mapped to SILVA (V4) database. No differences existed in alpha or beta diversity. The predominant phyla were Firmicutes. Staphylococcus were the predominant genera. The small sample size may have resulted in the lack of observed differences. With the absence of any differences observed when analyzing the metadata, this study provides insights into the bacterial population of mares' milk through lactation. In the future, this data can be utilized to examine the early colonizers of the foal gastrointestinal tract and identify targets for probiotic or prebiotic supplementation.